Research on the Temperature and Thermal Stress of the Roll Quenching Process of Thin Plates - Jianhui Wang; Xuetong Li; Kesong Yi; Sahal Ahmed Elmi (Metals, 2024)
The roll quenching process can be approximated as a high-pressure jet impinging on a high-temperature moving steel plate. The process can greatly improve the strength and overall mechanical properties of the steel plate. However, the cooling uniformity and other factors lead to the problem of poor plate shape after quenching. It is found that in the roll quenching process, the roller conveyor speed has a large influence on the temperature field and stress field. This paper establishes a roll quenching mechanism model, iterates the convective heat transfer coefficient on the steel plate surface through the inverse heat transfer method, and performs a numerical simulation. Through the numerical simulation of the roll quenching process in the high-pressure zone of the steel plate, the temperature and equivalent force change rule of the transient of each position of the steel plate in the thick direction are obtained. It is found that the plate does not reach its maximum value when it is in the quenching zone, but there is some hysteresis that becomes more pronounced as it gets closer to the core. These findings are valuable for regulating the roll-hardening process and maintaining optimal strip surface quality in industrial production environments.